A systematic review of cost-effectiveness, comparing traction to intramedullary nailing of femoral shaft fractures, in the less economically developed context. Issue 3 (25th September 2017) - Parkes, Rebekah J; Parkes, Gary; James, Kyle
Abstract : Introduction: Femoral shaft fractures carry considerable morbidity and are increasingly common in less economically developed countries (LEDCs). Treatment options include traction and intramedullary (IM) nailing but in a limited-resource environment; cost-effectiveness is fundamental to policy development. The objective herein was to evaluate the cost-effectiveness of moving from traction to IM nailing for femoral shaft fractures, in adults, in LEDCs. Incorporating a systematic review of complications and functional outcomes and a cost-minimization analysis. Methods: PubMed, EMBASE, Africa Journals Online and the Cochrane Library were searched from inception using the terms: femur* AND fracture AND traction AND (sign OR nail* OR intramedullary) AND (cost-effectiveness OR cost* OR outcome OR function) NOT paed* NOT child* NOT elastic NOT neck NOT intertrochanteric NOT periprosthetic (where asterisks indicate an unlimited truncation strategy). Abstracts were reviewed for all titles returned and full texts obtained as indicated. References of all relevant papers were also examined for further studies. Results: IM nailing has been successfully used in several institutions and reported infection, union and reoperation rates are encouraging, although no randomised control trials were identified. Three studies assessed the cost aspect and all found IM nailing to be the cheaper strategy. Conclusion: To date, the improved complication profile and reduced cost of treatment suggest that IM nailing is more cost-effective than traction. Evidence, however, is limited and the necessity for appropriate training and audit with the introduction of new techniques must be emphasised.